(NsISTEMA DOMA[NIH ZANQTIJ SKRIPA^As (Nu^EBNOE POSOBIEs - (NmOSTRAS(B.(Nk(B.(Ng(B.s ((NsANKT(B-(NpETERBURGs (NlANXs (NpLANETA mUZYKIs, 2024)
(NmOSTRAS kONSTANTIN gEORGIEWI^ (B1886-1965-(NROSSIJSKIJ SOWETSKIJ SKRIPA^ I MUZYKALXNYJ PEDAGOG(B.s
Keywords: (NmETODIKAs